Examining the reasons for missed nursing care from the viewpoints of nurses in public, private, and university hospitals in Jordan: A cross-sectional research. Issue 1 (February 2023) - Albsoul, Rania Ali; Alshyyab, Muhammad Ahmed; Hughes, James A.; Jones, Lee; FitzGerald, Gerard
Abstract: Background: Missed nursing care is an indicator of quality nursing care. It is a significant healthcare delivery problem, especially given increased demand and limited resources worldwide, including in Jordan. It is paramount to identify the reasons for missed care in hospital settings. Aim: To identify the perceptions of registered nurses for missed nursing care in medical and surgical wards in Jordanian hospitals. We also aimed to identify differences in the reported reasons for missed nursing care across three healthcare sectors: public, private, and university. Methods: A quantitative approach utilising a cross-sectional design was conducted by surveying registered nurses at 10 hospitals in Jordan. This study employed the MISSCARE Survey tool. The data collection was performed between March and July 2021. Descriptive statistics and analysis of variance were used to address the objectives. Findings: A sample of 672 registered nurses working in medical and surgical wards in 10 acute care hospitals in Jordan were recruited. The major reason for missed nursing care was inadequate number of staff. Communication issues were more important to missed nursing care in university hospitals than public and private hospitals. Conclusion: A study of Jordanian registered nurses revealed that a perceived shortage of human resources is the principal reason for missed nursing care in medical and surgical wards. Comparing the reasons for missed nursing care between the three hospital sectors could help nursing administrators to tailor operational interventions to mitigate the effect of these causes. Therefore, reducing missed nursing care.